Coupled CRLH transmission lines for compact and high selective bandpass filters. Issue 6 (30th March 2017) - Ibrahim, Ahmed A.; Abdalla, Mahmoud A.; Budimir, Djuradj
ABSTRACT: A compact size and high selective bandpass filter is presented in this paper. The filter is designed to serve at 3.5 GHz with two transmission zeros at 3.35 GHz and 3.85 GHz. The filter is designed as two gap capacitor coupled to two coupled composite right–left handed transmission lines. The coupled lines were designed to demonstrate a zeroth order phase at 3.5 GHz. Also, the transmission zeros were achieved as a consequence of the electrical/magnetic couplings between the two coupled transmission lines. The employed cell, filter design equations are emphasized. The filter S ‐parameters were extracted based on the circuit model, full wave simulation, and experimental measurements. A good agreement between modeled, simulated, and measured results is achieved. The measured center frequency of the bandpass filter is 3.55 GHz and 100 MHz bandwidth which is suitable for WiMAX applications. Also, the filter has low measured insertion loss which does not exceed 1 dB within passband. Finally, the filter has advantages of compactness (size is 20 × 18 mm 2 ) which is only 50% compared to conventional non‐selective one‐stage coupled line filter. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1248–1251, 2017